EUPHEMISMS, AS LINGUISTIC PHENOMENA (Web of Teachers: Inderscience Research, 2025)
Euphemisms are an essential aspect of various linguistic disciplines, serving as a vivid example of how language adapts to changes in social, cultural, and psychological spheres. In recent decades, advances in technology and interaction with informatics have allowed linguistics to explore new approaches to language analysis, including the study of euphemisms through computational linguistics and big data analysis. This study examines the theoretical foundations of euphemisms, their linguistic and cultural functions, and their role across languages. Particular attention is paid to cross-cultural comparisons between English, Russian, and Uzbek languages, highlighting universal and culture-specific characteristics of euphemization.